DIVERSITY OF AQUATIC FUNGI IN DIFFERENT PONDS OF RAIPUR, CHHATTISGARH, INDIA - Sharma, Kavita (LIFE: International Journal of Health and Life-Sciences, 2016)
Eight aquatic fungi were identified in water samples collected from different ponds of Raipur city during the period November 2013 to October 2014. The physicochemical characteristics of the collected water samples were also taken. The fungal population showed marked vertical variations during the period of study. The study gives important information about how moulds are distributed in the water, which will be important to consider in management of water contamination problems.